World Englishes: Speaking with Accents - Zelly Putriani; Riza Amelia; Harum Natasha; Kurnia Budiyanti; Riri Fauzana; Mainar Fitri; Nurdiana; Rizki Fiprinita; Roswati; Nurhayati (Anotero Lembaga Scientific Pekanbaru, 2021)
It is important to have the skill of conversation in English. However, learning it becomes definitely challenging when it is learned in foreign language context. It needs confidence and motivation. In this community service activity, there were 564 participants involved. Through the activity, the participants were encouraged to keep learning speaking English by helping and educating them to: (1) identify the sources of reluctance that prevent them using English actively, (2) reflect on the ways to overcome their reluctance to speak English, (3) find ways that they have not done before to do English conversation better, (4) increase their confidence in speaking English, (5) enlarge their knowledge about good English, (6) enlarge their knowledge about English as an international language versus English native speakerism. The activity was done in two ways; teaching and training packaged in webinar form. Last, this community service results on the participants’ satisfaction on the overall item evaluation administered. It is indicated by the result of post activity survey analysis showing very satisfactory level (mean >=4).